2013
DOI: 10.1111/joss.12038
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Decision Strategies Adopted in Reminder Tasks by Trained Judges When Discriminating Aqueous Solutions Differing in the Concentration of Citric Acid

Abstract: Four sensory difference tests -A-Not A, two-alternative forced choice (2-AFC) and their reminder counterparts, A-Not A with reminder task (A-Not AR) and 2-AFC with reminder task (2-AFCR) -were applied to pairs of aqueous solutions containing different concentrations of citric acid to determine the decision strategy adopted by judges in the reminder tasks, and which of the four tasks has the greatest test sensitivity. Three solution types, each containing a different number of compounds, were employed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Yet, in recent publications, the relative efficiencies of different overall discrimination test methods have been actively discussed using only a fixed design where the stimuli to be http://dx.doi.org/10.1016/j.foodqual.2015.06.021 0950-3293/Ó 2015 Elsevier Ltd. All rights reserved. discriminated from each other include only a pair of stimuli (2 stimulus types) (Choi, Kim, Christensen, van Hout, & Lee, 2014;Ennis & Christensen, 2014a, 2014bKim, Chae, van Hout, & Lee, 2014;McClure & Lawless, 2010;Olivas, Lopez-Malo, Angulo, & O'Mahony, 2014;Stocks, van Hout, & Hautus, 2013, 2014van Hout, Hautus, & Lee, 2011). Also, the relative test power of the various discrimination test methods have been only investigated based on the same numbers of tests (Bi, 2011;Ennis, 1993;Ennis & Jesionka, 2011;Jesionka, Rousseau, & Ennis, 2014;Kim et al, 2014;Schlich, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…Yet, in recent publications, the relative efficiencies of different overall discrimination test methods have been actively discussed using only a fixed design where the stimuli to be http://dx.doi.org/10.1016/j.foodqual.2015.06.021 0950-3293/Ó 2015 Elsevier Ltd. All rights reserved. discriminated from each other include only a pair of stimuli (2 stimulus types) (Choi, Kim, Christensen, van Hout, & Lee, 2014;Ennis & Christensen, 2014a, 2014bKim, Chae, van Hout, & Lee, 2014;McClure & Lawless, 2010;Olivas, Lopez-Malo, Angulo, & O'Mahony, 2014;Stocks, van Hout, & Hautus, 2013, 2014van Hout, Hautus, & Lee, 2011). Also, the relative test power of the various discrimination test methods have been only investigated based on the same numbers of tests (Bi, 2011;Ennis, 1993;Ennis & Jesionka, 2011;Jesionka, Rousseau, & Ennis, 2014;Kim et al, 2014;Schlich, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…The observers at our study site were highly trained, but their judgments were, by necessity, based on incomplete physical evidence. All human judgments are subject to some degree of error (Harris, 1915;Diefenbach, Brauning & Mattice, 2003), even in skilled observers (Taylor, Skourides & Alvero, 2012;Stocks, van Hout & Hautus, 2013). However, it is unlikely that the disagreement or detection differences were due entirely to human error.…”
Section: Discussion and Management Implicationsmentioning
confidence: 98%
“…more powerful than both specified and unspecified tetrad tests. For the 2-AFCR method in SDT, either the 2-AFC β/τ-strategy or the 2-AFCR τ-strategy were proposed (Hautus et al, 2009), and recently, these models have been confirmed by using trained subjects who evaluated the samples over several days to discriminate various simple food systems in a fixed experimental design (Stocks, van Hout, & Hautus, 2013, Stocks, van Hout, & Hautus, 2014; van Hout, Hautus, & Lee, 2011).…”
Section: Introductionmentioning
confidence: 98%